Intervenção profissional do assistente social e as condições de trabalho no Suas The social worker's professional intervention and working conditions at Suas - Raquel Raichelis (Serviço Social & Sociedade, 2010)
Este artigo tem por objetivo discutir o trabalho do assistente social no âmbito do Sistema Único de Assistência Social (Suas), enquanto espaço sócio ocupacional do assistente social e de outros profissionais, que amplia o mercado de trabalho e abre novas possibilidades de intervenção profissional, ao mesmo tempo em que precariza e intensifica os processos de trabalho, tensionando as formas de efetivação do projeto ético político profissional do serviço social. This article aims at discussing the professional practice of the social worker in the context of the Sistema Único de Assistência Social - Suas. It intends to address the system as a socio occupational space for social workers and other professionals, which enhances the labor market and opens new possibilities for professional intervention. However, it takes place concurrently with the precarization and intensification of the working process, putting pressure on the strategies for the realization of the ethical political professional project of social work.